The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s00027-019-0690-8
|View full text |Cite
|
Sign up to set email alerts
|

CH4 oxidation in a boreal lake during the development of hypolimnetic hypoxia

Abstract: Freshwater ecosystems represent a significant natural source of methane (CH 4). CH 4 produced through anaerobic decomposition of organic matter (OM) in lake sediment and water column can be either oxidized to carbon dioxide (CO 2) by methanotrophic microbes or emitted to the atmosphere. While the role of CH 4 oxidation as a CH 4 sink is widely accepted, neither the magnitude nor the drivers behind CH 4 oxidation are well constrained. In this study, we aimed to gain more specific insight into CH 4 oxidation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 65 publications
3
15
0
Order By: Relevance
“…For waterbodies with anoxic hypolimnia, there is significant variability in the fraction of hypolimnetic GHGs that are directly emitted to the atmosphere vs. oxidized in the water column (CH 4 : Bastviken et al 2008;Vachon et al 2019;Saarela et al 2020) or taken up by phytoplankton (CO 2 : Balmer and Engel et al 2019). Encinas Fernández et al (2014 estimated that up to 50% of the total hypolimnetic CH 4 stored in anoxic hypolimnia is directly released to the atmosphere during turnover.…”
mentioning
confidence: 99%
“…For waterbodies with anoxic hypolimnia, there is significant variability in the fraction of hypolimnetic GHGs that are directly emitted to the atmosphere vs. oxidized in the water column (CH 4 : Bastviken et al 2008;Vachon et al 2019;Saarela et al 2020) or taken up by phytoplankton (CO 2 : Balmer and Engel et al 2019). Encinas Fernández et al (2014 estimated that up to 50% of the total hypolimnetic CH 4 stored in anoxic hypolimnia is directly released to the atmosphere during turnover.…”
mentioning
confidence: 99%
“…2A and B ), which agrees with the measured rates of potential CH 4 oxidation (Saarela et al . 2020 ). In Lovojärvi, δ 13 C and concentration data suggested that CH 4 oxidation took place around the oxic-anoxic interface as well as deeper in the hypoxic and anoxic water column between 11.9 m and 5.9 m; however, confirmation of CH 4 oxidation at the deeper zone would require additional analyses, as the change in δ 13 C of CH 4 in the deeper zone was actually very slight (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Data from Lake Kuivajärvi for four sampling occasions from May to September 2016 were already presented in a previous paper (Saarela et al . 2020 ). However, in this paper, data are presented for September to allow for easier comparison with the microbial data.…”
Section: Methodsmentioning
confidence: 99%
“…Methane is mainly produced in the bottom sediments and/or hypolimnion, where most of anaerobic decomposition of organic matter take place, and then is either oxidized to CO2 in the water column or emitted to the atmosphere. At Kuivajärvi, a typical meso humid lake located in Southern Finland, it was found that 91% of available CH4 was oxidized in the active CH4 oxidation zone during hypolimnetic hypoxia (Saarela et al, 2020). In warm springs, the early onset of thermal stratification with cold and well-oxygenated hypolimnion delays the period of hypolimnetic hypoxia and thus limiting the production of methane.…”
Section: Lake Carbon Balancementioning
confidence: 99%